Analysis of the Relationship between Waste Management Systems and Dengue Fever Cases - Puteri Raniah; Yislam Junaid (Generasi Sains Indonesia, 2025)
Dengue fever remains a major public health challenge in rapidly urbanizing tropical regions, where environmental conditions significantly influence disease transmission. This study aims to examine the relationship between urban waste management systems and dengue fever incidence in Jakarta, Surabaya, and Bandung during the 2018–2023 period. A sequential explanatory mixed-methods approach was employed, integrating epidemiological data, waste management indicators, spatial analysis, field observations, and stakeholder interviews. The findings reveal that waste collection frequency and municipal service coverage are negatively associated with dengue incidence, whereas ineffective waste segregation contributes to increased mosquito breeding opportunities. Spatial analysis identifies significant clustering of dengue cases in areas characterized by waste accumulation and inadequate environmental infrastructure. The findings highlight the importance of combining waste management, community participation, and institutional coordination to strengthen dengue prevention. These results provide practical guidance for urban policymakers seeking sustainable and environmentally informed public health interventions.